2010
DOI: 10.1021/om100302g
|View full text |Cite
|
Sign up to set email alerts
|

Iridium Complexes of CCC-Pincer N-Heterocyclic Carbene Ligands: Synthesis and Catalytic C−H Functionalization

Abstract: A series of four meta-phenylene-bridged bis-benzimidazolium chlorides were synthesized as precursors to rigid, monoanionic, CCC-pincer N-heterocyclic carbene ligands. For ligands with mesityl, 3,5-xylyl, or 3,5-di-tert-butylphenyl side groups, reaction with [Ir(1,5-cyclooctadiene)Cl] 2 in acetonitrile with either excess triethylamine or stoichiometric cesium fluoride as base gave neutral, iridium(III) pincer complexes of the formula Ir(CCC)HCl(MeCN), which were purified by chromatography on silica gel. Metalat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(79 citation statements)
references
References 110 publications
(45 reference statements)
3
75
1
Order By: Relevance
“…There are, however, reports of alkane dehydrogenation catalyzed by non-phosphine-based pincer-iridium complexes, mainly based on NCN [92,93] and CCC [84,[94][95][96] pincer motifs. Goldberg and coworkers have recently reported the use of a NCN-type pincer-type complex, ( dm Phebox)Ir(OAc) 2 (OH 2 ) (36) for the stoichiometric dehydrogenation of n-octane at 200 C resulting in the formation of ( dm Phebox)Ir(OAc)(H) (61) and octenes (7) [93].…”
Section: ð5þmentioning
confidence: 99%
“…There are, however, reports of alkane dehydrogenation catalyzed by non-phosphine-based pincer-iridium complexes, mainly based on NCN [92,93] and CCC [84,[94][95][96] pincer motifs. Goldberg and coworkers have recently reported the use of a NCN-type pincer-type complex, ( dm Phebox)Ir(OAc) 2 (OH 2 ) (36) for the stoichiometric dehydrogenation of n-octane at 200 C resulting in the formation of ( dm Phebox)Ir(OAc)(H) (61) and octenes (7) [93].…”
Section: ð5þmentioning
confidence: 99%
“…In addition to simple alkane dehydrogenation, these complexes have been employed for numerous other catalytic transformations of hydrocarbons, including alkane metathesis, 6,8,9,20,[24][25][26] alkyl group metathesis, 27 dehydroaromatization, 19,28,29 alkanealkene coupling reactions, [30][31][32] borylation of alkanes 23 and the dehydrogenation of several non-alkane substrates. 22,33,34 Several pincer motifs more recently explored, such as (CCC)Ir, [35][36][37][38] (PCP)Ru 39-41 , (PCP)Os 42 , and (NCN)Ir 43,44 have been found to show promise for alkane dehydrogenation but as of yet none have proven to be competitive with the well investigated PCP-type iridium-based systems. 26 In early alkane dehydrogenation studies 45 3,3-dimethyl-1-butene (TBE) was found by Crabtree to be a singularly effective hydrogen acceptor.…”
Section: Introductionmentioning
confidence: 99%
“…The CCC iridium complexes 28 containing bis-Nheterocyclic carbenes were prepared by Chianese et al [81][82][83]. These complexes are active for acceptorless dehydrogenations of both linear and cyclic alkanes, albeit with lower activity compared with the classical PCP or POCOP systems (Eq.…”
Section: ð22þmentioning
confidence: 99%